PENGUKURAN EARNED VALUE ANALYSIS SEBAGAI EARLY WARNING SIGNS PADA PROYEK KONSTRUKSI - Khiyana, A'izzatul; Sundari, Titin; Yulianto, Totok; Nugroho, Meriana Wahyu; Agung, Achmad Imam (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2024)
The basic concepts of earned value analysis can be utilised to evaluate performance and forecast the achievement of objectives, particularly in relation to cost and time. Systematic cost and time control is essential to ensure that the project execution time is in accordance with the contract, or even faster, so that costs can be minimised to avoid sanctions due to delays. The objective of this study is to evaluate time and cost performance using the calculated earned value analysis method and analyse the causes of delays and cost overruns. The method applied in this research is Earned Value method, with data of S-Curve, Budget Plan of Cost (RAB), project weekly report, and actual cost. The results showed that the project was delayed by 2 weeks, bringing the total completion time to 25 weeks. The main cause of the delay was caused by changes in the scope of work during implementation, while cost overruns occurred due to work that was not in accordance with the predetermined schedule.